Social media use and cross-cultural adaptation of Chinese students overseas: a systematic review - Bi, Shanshan; Abdul Latiff Ahmad,; Jamaluddin Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Due to the progress of globalization, as well as the advancement of transportation and communication tools, there is a greater interconnectedness among nations and regions worldwide. A common trend of it is the increasing prevalence of students opting to pursue tertiary education overseas. Asia has emerged as the largest exporter, sending the largest proportion of international students to the world, especially China. When studying in foreign countries, international students may encounter challenges from life and studies; then, social media has become a pivotal tool in their lives for obtaining information and interpersonal communication. This study intends to conduct a systematic review of the influence of social media on the cross-cultural adaptation of Chinese overseas students, who constitute the largest cohort of international students, and adopts databases Web of Science, Scopus and ScienceDirect. From 2014 to 2023, 15 studies met the inclusion criteria. The United States was the most studied geographic country, and most studies delved into cross-cultural adaptation from socio-cultural and psychological aspects, with less research from the academic aspect. Besides, these studies largely proved the positive role of social media in facilitating the attainment of social capital and enhancing psychological well-being among Chinese overseas students. Nevertheless, a few studies also showed the drawbacks of social media use. There is a call for studies on the correlation between academic adaptation of Chinese overseas students and social media use, as well as to explore international students’ proper use of social media.